(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Ohm’s Law has long been a cornerstone of electrical engineering, providing a linear relationship between voltage, current, and resistance that has underpinned modern circuit analysis. However, as technology advances and philosophical inquiries deepen, the limitations of this venerable law have become evident, particularly in scenarios involving near-zero resistance. This paper introduces a novel formulation-the modified Ohm’s Law; that not only rectifies the pitfalls of the conventional law but also harmonizes physics with philosophical principles. Motivated by the perplexing issue of predicting infinite current at zero resistance and the philosophical implications of deriving infinity from the finite, the modified equation serves as a bridge between empirical insights and logical coherence. Through rigorous mathematical derivation, comprehensive theoretical examination, and scrupulous computational analysis, the accuracy and applicability of the modified Ohm's Law are not only demonstrated but also its suitability across a wide range of scenarios is revealed. These scenarios include semiconductor devices, high-current applications, and complex systems where the standard Ohm’s Law falls short, offering a transformative perspective on the analysis of electrical circuitry. In reconciling scientific rigor with philosophical consistency, this paper advances our understanding of electrical circuitry and beckons a newera of precision in analysis. Further, the modified Ohm’s Law paves the way for deeper explorations that resonate through the domains of physics and philosophy, reshaping the landscape of our understanding